Pseudomonas aeruginosa infection in cystic fibrosis patients - Ahmed, Syed AK Shifat; Dooley, James SG; Deb, Sudip Ranjan; Talukder, Debesh Chandra; Hossain, Sheikh Shahinoor; Anwar, ASM Tanim (Journal of Dhaka Medical College, 2013)
Cystic Fibrosis is an autosomal recessive genetic disease where the lung is heavily colonized by biofilm forming Pseudomonas aeruginosabacteria. Biofilm due to its thick wall and presence of extracellular polymeric substances confers bacteria with a much higher resistance against antimicrobial compounds and environmental stress. Research has revealed the presence of extracellular DNA (eDNA) in significant amounts in the biofilm walls of such bacteria. Although the exact role of eDNA has not been elucidated but research prompts that eDNA to have significant role in stabilizing the biofilm complex structure as well as providing the bacteria with resistance against antimicrobial and antibiotic compounds. The presence of eDNA prompted research to use DNase as a biofilm destabilizing agent. Under experimental conditions, DNase has shown to dissolve early forming biofilm walls especially when used in combination with antibiotics therefore suggesting the use of DNase as an effective treatment strategy in CF patients. But ambiguity arises when some recent studies showed that P. aeruginosa can opportunistically use DNase for its survival advantage by using the enzyme to access phosphate, carbon and nitrogen constituentsof the DNA in nutrient limited conditions; and also by using the DNase to degrade the DNA component of neutrophil extracellular traps. These apparent contradictions call for more thorough investigations into the role of eDNA and DNase in CF biofilm infection. DOI: http://dx.doi.org/10.3329/jdmc.v22i1.15689 J Dhaka Medical College, Vol. 22, No. 1, April, 2013, Page 77-86